Optimizing Total Quality Management Using Information Systems to Enhance Stakeholder Satisfaction at Madrasah Aliyah - Khansa Ayu Fatimah; Wina Yulianti (AIM: Journal of Islamic Education Management, 2026)
The quality of education in Indonesian Islamic educational institutions, particularly Madrasah Aliyah, remains a persistent challenge in the era of global competition. This study investigates the optimization of Total Quality Management (TQM) integrated with Management Information Systems (MIS) to enhance stakeholder satisfaction at Madrasah Aliyah Negeri (MAN) 2 Bandung. Employing a qualitative case study approach, data were collected through in-depth interviews, observation, and documentation involving principals, teachers, administrative staff, students, and parents as research participants. The findings reveal that: (1) MAN 2 Bandung has implemented TQM principles encompassing customer focus, total involvement, measurement, commitment, and continuous improvement, supported by digital MIS infrastructure; (2) the primary drivers of suboptimal TQM implementation include inconsistent leadership commitment, limited digital literacy among staff, and fragmented information systems; and (3) the integration of MIS into TQM processes has demonstrably improved stakeholder satisfaction through enhanced service responsiveness, transparent communication, and data-driven decision-making. The study concludes that MIS-based TQM optimization constitutes a transformative strategy for madrasah quality management, with implications for policy development in Islamic education governance. Recommendations are directed toward strengthening digital infrastructure, building staff capacity, and institutionalizing quality culture across all organizational levels.